A Comprehensive Review on Ocimum basilicum - Purushothaman, Balakrishnan; PrasannaSrinivasan, Ramalingam; Suganthi, Purushothaman; Ranganathan, Balu; Jolius, Gimbun; Shanmugam, Kumaran (Informatics Publishing Limited, 2018)
The genus Ocimum has a number of species that are used to treat different types of disorders and diseases from ancient times. In this genus, O. basilicum plays a vital role due to its various medicinal properties. It is universally cultivated as herbaceous, perennial plant but originated from Asian continent. O. basilicum is used as a culinary herb and also has a number of pharmacological activities to prevent or treat cardiovascular disorders, diabetes, menstrual cramps, digestive disorders, neuro-degenerated disorders and cancer. In addition to that, it has been reported for antioxidant, antimicrobial, and larvicidal activities. Chemical constituents such as linalool; eugenol; 1, 8-cineone; methyl eugenol and anthocyanins are mostly responsible for the above mentioned activities. Some traditional uses of this plant coincidences with experimental results. However, the studies conducted based on its traditional use are negligible. This review is an attempt to provide a pharmaceutical perspective of Ocimum basilicum.